UNCERTAINTY AND RISK ANALYSIS IN THE CONSTRUCTION SCHEDULE OF SDN SUKATANI 7 - Christian Sitompul, Nico
The high population in Indonesia leads to increased demand for infrastructure. One such need is for school buildings, exemplified by SDN Sukatani 7. The planning and execution of the SDN Sukatani 7 construction project are influenced by time, quality, and cost. Time is the aspect with the highest risk because it directly affects quality and cost. Therefore, it is crucial to plan the schedule of a construction project effectively. This research was conducted using interviews and the collection of project documents related to the construction of SDN Sukatani 7. Data including the cost budget plan, weekly reports, shop drawings, schedule, and technical specifications were used to determine the critical path of the project and to calculate the productivity of activities on the critical path. Interviews were then conducted and data were processed using the Analytical Hierarchy Process (AHP) method to determine the weighting of hazard factors, followed by further interviews to assess the magnitude of risk factors and schedule uncertainty projections to obtain the probability of project schedule failure. Based on the calculations, it was found that the project schedule for SDN Sukatani 7 has a total risk score of 14.3238 out of a possible 25. This risk is categorized as moderate. A project duration of 200 days has a 5% probability of failure, while a duration of 184 days has a 50% probability of failure.